Hydrologic dataset extraction around the downstream portion of Cabulig watershed using Lidar derived Digital Elevation Model (DEM) - Villar, Ricardo G.; Ruta, Jerald L.; Bantugan, Jojemar; Barbadillo, Nycel S.; Opiso, Einstine M.; Aquino, Jean; Pelayo, Jigg L. (2016)
Digital Elevation Models (DEMS) processed through the combined application of Remote Sensing (RS) and Geographic Information System (GIS) technologies were the most critical datasets to the success of surface hydrologic modelling applications. This study aims to extract the hydrologic features like drainage line, inland wetlands and irrigations of Cabulig watershed using available LiDAR datasets. WhiteboxGAT and QuantumGIS were used to extract wetlands and irrigation while ArcGIS software was used for streams. The extracted features were validated using ancillary maps and Google Earth while features that are not clear were assigned as Point of interest (POI) and were subjected for ground validation. Aside from POI, random sampling tool was used to generate points subject for field validation. The results showed that the extracted features have higher average accuracy in comparison to the data obtained from the field regardless of specific type of hydrologic features. The extracted streams network using ArcGIS showed the highest accuracy while the extracted wetlands features using the combined applications of WhiteboxGAT and QuantumGIS showed relatively lower accuracy. Therefore, this study was able to extract the hydrologic features of Cabulig watershed using LiDAR-derived DTMs with higher levels of accuracy compared to lower resolution DEMs.
Keywords: Cabulig watershed (Misamis Oriental); Water resource mapping; Water resource inventory; Light Detection and Ranging; Mindanao studies